2014
DOI: 10.16949/turcomat.64904
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Misconceptions of Nine Grade Students on Repeating Decimals

Abstract: Bu çalışmanın amacı, dokuzuncu sınıf öğrencilerinin devirli ondalık gösterimle ilgili kavram yanılgılarını belirlemektir. Çalışmanın amacı doğrultusunda kavram yanılgısı türleri göz önüne alınarak devirli ondalık gösterim ilgili olası kavram yanılgılarına yönelik açık uçlu sorular içeren "Devirli Ondalık Gösterim Tanı Testi" hazırlanmış ve dokuzuncu sınıfta okuyan kırk öğrenciye uygulanmıştır. Öğrencilerden alınan yanıtlar detaylı olarak incelenerek öğrencilerin kavram yanılgıları aşırı genelleme, aşırı özelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Hence, the researcher rejects the null hypothesis, which assumed no difference between learners taught with group investigation and those taught with the lecture-based approach. The study findings that showcased a superior concept mastery performance for learners taught using the group investigation method is congruent with previous studies (Adiansyah et al, 2017; Baki et al, 2010; Girsang, 2014; Parchment, 2009; Tran & Lewis, 2012a, 20212bbib_Tran_and_Lewis_2012abib_Tran_and_Lewis_2012b). The above-cited studies revealed that when learners are taught using a group investigation instructional approach, they perform better on their concept mastery skills than those taught with the traditional lecture approach.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Hence, the researcher rejects the null hypothesis, which assumed no difference between learners taught with group investigation and those taught with the lecture-based approach. The study findings that showcased a superior concept mastery performance for learners taught using the group investigation method is congruent with previous studies (Adiansyah et al, 2017; Baki et al, 2010; Girsang, 2014; Parchment, 2009; Tran & Lewis, 2012a, 20212bbib_Tran_and_Lewis_2012abib_Tran_and_Lewis_2012b). The above-cited studies revealed that when learners are taught using a group investigation instructional approach, they perform better on their concept mastery skills than those taught with the traditional lecture approach.…”
Section: Discussionsupporting
confidence: 91%
“…The current research emerged from the researcher's experience as a teacher, an analysis of the rationale of the Ghanaian middle school social studies standard, and initial interview findings from some Ghanaian social studies teachers who confirmed that they mostly used lecture-based instruction despite the stated rationale of the social studies syllabus. Whereas other existing literature discovered the group investigation outperformed the lecture-based group, the previous research focused on reading comprehension, critical thinking, literature, and other areas (Adiansyah's et al, 2017;Baki et al, 2010;Parchment, 2009;Tran & Lewis, 2012a;Tran & Lewis, 2012b). The present study adds to the literature on social studies as a discipline by bringing to the forefront that group investigation as an instructional approach significantly differs from lecture-based instruction in contributing to learners' concept mastery and transferability in social studies content.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, it has advantages including increasing independence, increasing student creativity, increasing interpersonal skills when working between students, increasing student reasoning (Christina & Kristin, 2016). This model is believed to improve process and outcome of learning (Astra, Wahyuni, & Nasbey, 2015) and can be integrated in language learning (Baki, Yildiz, Aydin, & Kogce, 2010).…”
Section: Introductionmentioning
confidence: 99%